2023
DOI: 10.3390/nu15245079
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) Is the Strongest Predictor of Systemic Hypertension and Cardiac Mass in a Cohort of Children

Marianna Fabi,
Matteo Meli,
Davide Leardini
et al.

Abstract: Background: Hypertension (HTN) is a well-established cardiovascular (CV) risk factor in adults. The presence of HTN in children appears to predict its persistence into adulthood. Early diagnosis of HTN is crucial to reduce CV morbidity before the onset of organ damage. Aim: The aim of this study is to investigate cardiac damage in HTN, its risk factors (RFs), and evolution. Methods: We conducted a prospective/retrospective study involving children referred to the Childhood Hypertension Outpatient Clinic. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The main study findings can be summarized as follows. First, confirming recent findings [ 8 , 9 , 11 , 22 ] markers of obesity such as body weight, BMI and waist circumference are strongly correlated LVMI in a pediatric population homogeneous in terms of biochemical profile and BP parameters. Second, the correlation was detected not only with left ventricular mass, but also with left atrial dimensions and RWT, i.e.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main study findings can be summarized as follows. First, confirming recent findings [ 8 , 9 , 11 , 22 ] markers of obesity such as body weight, BMI and waist circumference are strongly correlated LVMI in a pediatric population homogeneous in terms of biochemical profile and BP parameters. Second, the correlation was detected not only with left ventricular mass, but also with left atrial dimensions and RWT, i.e.…”
Section: Discussionsupporting
confidence: 86%
“…However, the relative contribution of hemodynamic vs non-hemodynamic factors at the development of the above mentioned association remains at present unsettled, due to heterogeneity of the populations examined as well as to the presence of confounding factors [ 10 ]. A prospective/retrospective study very recently suggested the importance of body weight as determinant of left ventricular mass in a cohort of children [ 11 ].…”
Section: Introductionmentioning
confidence: 99%